A research and development study of a game-based learning model: Effects on basketball skills and engagement in physical education - Perdima, Feby Elra; Sofyan, Davi; Sulastio, Agus (UIR Press, 2026)
Background: Traditional basketball instruction often emphasises isolated technical drills with limited game-based participation, which may reduce student engagement and hinder skill development. Despite growing interest in game-based learning (GBL), there is limited evidence on structured GBL models in higher education contexts, particularly in Indonesia. Objectives: This study aimed to develop and evaluate a game-based learning model to improve basketball skills and student engagement in physical education. Methods: A research and development (R&D) approach, adapted from Borg and Gall’s model, was employed, encompassing needs analysis, model design, expert validation, and field trials. The model’s effectiveness was assessed using a one-group pretest–posttest design with purposively sampled physical education students. Data were collected through standardised basketball skill tests (dribbling, passing, shooting), questionnaires, and interviews. Quantitative data were analysed using paired-sample t-tests (p < .05), while qualitative data were examined using thematic analysis. Results: In the small-scale trial (n = 30), students’ performance improved by 23.9% from pretest to posttest, with statistically significant differences and large effect sizes. The large-scale trial (n = 60) further confirmed the model’s effectiveness, showing significant improvements in basketball skills (t = 12.44, p < .001). Students also reported highly positive perceptions (M = 4.68, SD = 0.41), indicating strong engagement and acceptance of the GBL approach. Conclusion: The developed GBL model effectively enhances basketball skills, engagement, and learning experiences among physical education students. These findings support the integration of game-based approaches in sports instruction and highlight their potential for broader application in physical education contexts. Future research should examine long-term effects and applicability across different sports settings.